Natural gas origin and accumulation of the Changxing–Feixianguan Formation in the Puguang area, China - Li Songfeng; Liu Xiaoxia; Zhang Peixin; Zhao Yinan (Open Geosciences)
Investigating the origin and accumulation of natural gas is crucial for investigating fields of gas and oil. This study can provide effective guidance for future strategic decisions. In this study, the Changxing–Feixianguan Formation gas reservoir in the Puguang area was employed as a case study. The gas source strata were evaluated through analysis of the geochemical characteristics of natural gas. The period of accumulation and reservoir type were identified by examining the inclusion and burial history characteristics. The results revealed that (1) the Changxing–Feixianguan Formation was a high-sulfur gas reservoir, primarily characterized by oil-type gas. Influenced by thermal sulfate reduction, it exhibited partial characteristics of a mixed gas; (2) the natural gas of the Changxing–Feixianguan Formation demonstrated a favorable biogenic relationship with the carbon isotope characteristics of the Longtan Formation and Maokou Formation kerogen, and its primary gas source was Permian source rock; and (3) the Changxing–Feixianguan Formation gas reservoir experienced three oil and gas charging events, namely, the Middle Triassic, Late Jurassic, and Late Cretaceous. Natural gas was primarily extracted from ancient reservoirs and has evolved into light oil, condensate gas, wet gas, and dry gas. These findings serve as a foundation for investigating the accumulation of natural gas within the Changxing–Feixianguan Formation in the Puguang area. In future natural gas exploration efforts, it is recommended to concentrate on identifying paleostructures that may have formed ancient oil reservoirs to enhance the precision of natural gas exploration.